2003
DOI: 10.1159/000076288
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome aberration dosimetry in cosmonauts after single or multiple space flights

Abstract: Background and aims: Cosmic radiation is one of the main hazards for manned space exploration. Uncertainty in radiation risk estimates for crews of long-term missions are very high, and direct biological measurements are necessary. We measured chromosomal aberrations in peripheral blood lymphocytes from 33 cosmonauts involved in space missions during the past 11 years. Methods: Blood lymphocytes from the cosmonauts were stimulated to grow in vitro and were harvested at their first mitosis. Slides were either s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 23 publications
(22 reference statements)
1
35
0
Order By: Relevance
“…Russian cosmonauts 57 show that the measured chromosomal rearrangements in crewmembers returning from space flight are consistent with current models, although the biological results are also affected by a large experimental uncertainty at low doses.…”
Section: Chromosomal Aberrationssupporting
confidence: 64%
See 1 more Smart Citation
“…Russian cosmonauts 57 show that the measured chromosomal rearrangements in crewmembers returning from space flight are consistent with current models, although the biological results are also affected by a large experimental uncertainty at low doses.…”
Section: Chromosomal Aberrationssupporting
confidence: 64%
“…Besides, for cosmonauts involved in multiple spaceflights, the total yield of aberrations do not seem to be additive 51 , and in experienced cosmonauts with a total of about 2 years in the final yield of the aberrations is close to the measured background before the first flight 57 . The significance of these findings remains to be elucidated.…”
Section: Chromosomal Aberrationsmentioning
confidence: 79%
“…It has been shown that the frequency of chromosome aberrations increases in astronauts blood lymphocytes after space flight (George et al, 2001 a and b;Federenko et al, 2001;Durante et al, 2003), and results indicate that biodosimetry estimates lie within the range expected from physical dosimetry and ICRP models, when samples are obtained shortly after flight .…”
Section: Introductionmentioning
confidence: 93%
“…In a recent study, a statistically significant increase in the yield of chromosomal aberrations in lymphocytes from cosmonauts at their first flight long-term space missions was observed. However, for cosmonauts involved in two or more space flights, the yield of aberrations at the end of the last mission was generally in the range of background frequencies measured before the first mission (Durante et al, 2003). This study suggests possible existence of AR induced by space irradiations in vivo.…”
Section: Discussionmentioning
confidence: 66%